-5x+6=-8y

Simple and best practice solution for -5x+6=-8y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x+6=-8y equation:


Simplifying
-5x + 6 = -8y

Reorder the terms:
6 + -5x = -8y

Solving
6 + -5x = -8y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -5x = -6 + -8y

Combine like terms: 6 + -6 = 0
0 + -5x = -6 + -8y
-5x = -6 + -8y

Divide each side by '-5'.
x = 1.2 + 1.6y

Simplifying
x = 1.2 + 1.6y

See similar equations:

| 16x^3-6x-x=0 | | p^2+12p+4=0 | | -5-x=2x-(4x+6) | | 2x^2-11x-1=0 | | 26x^2-35xy+11y^2=0 | | -10x+3=3x+12-4x | | 4x-5=18-7x | | 6(x+3)=-2x+10 | | 5m-7m=-6m-29 | | X^3+5x^2+5x+25=0 | | 4-4b= | | 12ab-3a-20b+5=0 | | 8m=152 | | Xy+3y-5x-15=0 | | 4b-4= | | 16xy+28x+12y+21=0 | | 3n=-15 | | 4c^2+27c+35=0 | | 27h^2=48h | | 2-5=0 | | 8Abc^2+4a^2bc+2bc=0 | | y=-3.5x+4 | | 8x-17=6x+15 | | 6m-8m+5= | | -4x^7y+6xy^8=0 | | 6p=4+p | | 4b^2-8b-5=0 | | 10a^5b^7+5ab^3-40ab^7=0 | | 6p=4-p | | x+(x+7)+(3x+8)= | | 2m-1=9 | | (5n-5)(6n-2)= |

Equations solver categories